1995
DOI: 10.1007/bf02245829
|View full text |Cite
|
Sign up to set email alerts
|

Subjective and objective symptoms in relation to plasma methadone concentration in methadone patients

Abstract: Two rating scales, which were originally developed for measurements of objective and subjective signs of opiate withdrawal, were used to evaluate potential estimates (correlates) of methadone effects in relation to plasma methadone concentrations. Patients participating in our regular methadone maintenance treatment project were studied during 24 h after the intake of the daily methadone dose. Methadone concentrations in plasma were compared to the subjective (estimated by the patients) and objective (estimate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0
1

Year Published

1999
1999
2016
2016

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(26 citation statements)
references
References 7 publications
1
24
0
1
Order By: Relevance
“…Detoxication after prolonged use in heavy users of coffee or of opiates is accompanied by the withdrawal syndrome of repetitive yawning over several days [43,44,45,46,47,48,49]. The clinical profile of a neonate with a mother who consumes opiates, legal (methadone, morphine) or not until the end of her pregnancy, can be impressive with respiratory irregularities and pauses interspersed with salvos of yawning [50, 51].…”
Section: Excessive Yawningmentioning
confidence: 99%
“…Detoxication after prolonged use in heavy users of coffee or of opiates is accompanied by the withdrawal syndrome of repetitive yawning over several days [43,44,45,46,47,48,49]. The clinical profile of a neonate with a mother who consumes opiates, legal (methadone, morphine) or not until the end of her pregnancy, can be impressive with respiratory irregularities and pauses interspersed with salvos of yawning [50, 51].…”
Section: Excessive Yawningmentioning
confidence: 99%
“…Methadone is transported in a single dose, reaching a maximum level six hours after use, which then falls continuously until 24 hours. On the other hand, nicotine is delivered in little quantities that reach the central nervous system rapidly and undergo rapid clearance in a period of 24 hours (Hiltunen et al, 1995). Moreover, oral methadone produces sedative effects, but nicotine acts as a stimulant; these antagonist actions may induce tobacco users to use tobacco as stimulant with the aim of counteracting the sedative properties from oral methadone by titrating nicotine levels as a response to increases in methadone doses and the day-to-day highest serum levels of methadone (Preston, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…Elderly methadone-dependent patients are more likely to be seen in geriatric settings (Miller 1991;Gurnack 2002), are less likely to request detoxification and tend to continue the dose of methadone that they received when they were younger (Hiltunen 1995;Gurnack 2002). Gurnack et al (2002) also reported that older patients on methadone maintenance tend to prefer higher doses.…”
Section: Opioidsmentioning
confidence: 99%